2020
DOI: 10.5334/tohm.560
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Responsive Hyperkinetic Movement Disorders—a Mechanistic Hypothesis

Abstract: Patients with essential tremor, vocal tremor, torticollis, myoclonus-dystonia and posthypoxic myoclonus often benefit in a surprisingly rapid and robust manner from ingestion of a modest amount of alcohol (ethanol). Despite considerable investigation, the mechanism of ethanol's ability to produce this effect remains a mystery. In this paper, we review the pharmacology of ethanol and its analogue GHB (or sodium oxybate), summarize the published literature of alcohol-responsive hyperkinetic movement disorders, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 74 publications
0
12
0
4
Order By: Relevance
“…This could also lead to an increase of corticospinal excitability due to the reduction of inhibitory influence of Purkinje cells on cerebello-thalamo-cortical pathways. The possibility of influencing Purkinje cells and/or inter-connected neuronal circuits non-invasively potentially has high clinical relevance, because especially the pathophysiology of alcohol-responsive movement disorders, e.g., essential tremor and myoclonus dystonia, seems to be related to activity of these cell types ( Frucht and Riboldi, 2020 ; Madelein van der Stouwe et al, 2020 ). All these models explain an effect of stimulation of the cerebellum via direct or indirect cerebello-neocortical projections.…”
Section: Discussionmentioning
confidence: 99%
“…This could also lead to an increase of corticospinal excitability due to the reduction of inhibitory influence of Purkinje cells on cerebello-thalamo-cortical pathways. The possibility of influencing Purkinje cells and/or inter-connected neuronal circuits non-invasively potentially has high clinical relevance, because especially the pathophysiology of alcohol-responsive movement disorders, e.g., essential tremor and myoclonus dystonia, seems to be related to activity of these cell types ( Frucht and Riboldi, 2020 ; Madelein van der Stouwe et al, 2020 ). All these models explain an effect of stimulation of the cerebellum via direct or indirect cerebello-neocortical projections.…”
Section: Discussionmentioning
confidence: 99%
“…SBX, a sodium salt of γ-hydroxybutyrate, has been traditionally used and approved for cataplexy in narcolepsy. However, this medication has been proven to be beneficial in alcohol-responsive movement disorders, such as tremor, post-hypoxic myoclonus, myoclonus dystonia, and spasmodic dysphonia [ 7 8 9 10 11 ]. In all of our patients, this treatment significantly improved quality of life, though one had to discontinue use due to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…A recent preclinical evidence demonstrated that adult mice with knockdown of Sgce in the cerebellum, but not in the basal ganglia, develop overt motor symptoms, including dystonia, which can be improved by administration of ethanol [ 101 ]. Moreover, very recently, Frucht and Riboldi proposed a model to explain the clinical improvement with low doses of EtOH in MD, supporting an abnormal activation of the Purkinje cells and dentate nucleus and a likely mechanism of action of EtOH to normalize abnormal cerebellar output in this disorder, paving the way for future speculation [ 102 ].…”
Section: Myoclonus‐dystonia and Alcohol Responsivenessmentioning
confidence: 99%
“…GHB is supposed to have a low affinity to the metabotropic GABA B receptor, either directly or via conversion to GABA [ 114 ] as well as an action via the GHB receptors that bind to extrasynaptic GABA A receptors [ 116 ]. However, other mechanisms of action may be involved, since other GABA B agonists, such as baclofen, have minimal effects on myoclonus [ 102 ]. A recent study on 531 patients with alcohol‐responsive laryngeal dystonia treated with SXB demonstrated an impressive improvement of dystonic symptoms, presumably as a result of the modulation of the abnormal plasticity within the cortical and subcortical circuitry [ 117 ].…”
Section: New and Old Drugs For The Treatment Of Myoclonus‐dystonia An...mentioning
confidence: 99%
See 1 more Smart Citation